Analisis Faktor Harga Terhadap Keputusan Pembeli Produk Kerupuk Udang Desa Punti - Jumriani Jumriani; Sulistianingsih Sulistianingsih; Annisa Annisa; Hawaria Hawaria; Agus Maulana; Nurfitrah Nurfitrah; Muhaimin Muhaimin; Ismunandar Ismunandar; Muhammad Badar (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
This research aims to analyze the influence of price on purchasing decisions for shrimp cracker products in Punti Village, Soromandi District, Bima Regency. By using primary data obtained through distributing questionnaires to consumers, this research identifies the relationship between price variables and purchasing decisions. The analysis results show that price does not have a significant influence on purchasing decisions, with a significance value greater than 0.05. Although the data used is reliable with 95.3% valid cases, the data distribution is not normal which can affect the analysis results. The multiple linear regression test and F test show that the regression model built is not significant, with only 2.5% of the variation in purchasing decisions that can be explained by price. These findings indicate the need for further research to explore other factors that might influence purchasing decisions for shrimp cracker products in Punti Village.